KARAKTERISTIK PENALARAN SISWA KELAS XI SEKOLAH MENENGAH ATAS TENTANG SAMPEL - Muhammad Saifuddin Zuhri (Jurnal Pembelajaran Matematika, 2013)
Abstract: This research aims to describe how the reasoning characteristics of the 11th students of Senior High School about samples. This study was a descriptive qualitative research. The subject of research was the 11th students of SMA Negeri 1 Purwodadi consisting of two students for each level of mathematics competency. The subject selection criteria were based on student mathematics competency and opinion expressing competency, either in spoken and written form. The data was collected using written test and interview technique. The data analysis was done based on the data on written test and interview results. Then the method triangulation was run to produce a valid data from the research subject. The result of research showed that the students with low mathematics competency were at level 1 with the following characteristics: the students can give example of sample, can describe term of sample, approve the small number of sample selection in the research, do not recommend appropriate selection in sample taking. The students with medium mathematics competency were at level 2 with the following characteristics: the students can give example about the sample, can describe term of sample, combine small size with appropriate selection methods or large sample size with inappropriate selection methods. Some students with high mathematics competency were at level 2 and some other were at level 3 with the following characteristics: the students can give example about sample, can describe term of sample, recommend of the larger size sampling from the population, recommend the selection through random sampling technique and can explain the procedures randomly, and can identify the potentially biased sampling in a research.Keywords: Reasoning, Reasoning about Sample, Sample Concept, Reasoning Characteristics about Sample.